International relations theory and South Asia security, political economy, domestic politics, identities, and images - Sridharan, E (Oxford University Press New York, 2011)
Revised version of papers presented at various conferences held between 2002 and 2006.
Keywords: South Asian cooperation -- Congresses; Security, International -- South Asia -- Congresses; Economics -- South Asia -- Congresses; South Asia -- Foreign relations -- Congresses; South Asia -- Politics and government -- Congresses